Object recognition tasks in rats: Does sex matter? - Becegato, Marcela; Silva, Regina H. (Frontiers in Behavioral Neuroscience, 2022)
Novelty recognition tasks based on object exploration are frequently used for the evaluation of cognitive abilities and investigation of neurobiological and molecular aspects of memory in rodents. This is an interesting approach because variations of the object recognition tasks focus on different aspects of the memory events such as novelty, location, context, and combinations of these elements. Nevertheless, as in most animal neuroscience research, female subjects are underrepresented in object recognition studies. When studies include females, the particularities of this sex are not always considered. For example, appropriate controls for manipulations conducted exclusively in females (such as estrous cycle verification) are not included. In addition, interpretation of data is often based on standardizations conducted with male subjects. Despite that, females are frequently reported as deficient and unable to adequately perform some memory tests. Thus, our study aims to review studies that describe similarities and differences between male and female performances in the different variations of object recognition tasks. In summary, although females are commonly described with deficits and the articles emphasize sex differences, most published data reveal similar performances when sexes are compared.